Beitragssatz, Kassenwettbewerb und Gesundheitsreform: Eine empirische Analyse - Hanfried H. Andersen; Markus M. Grabka; Johannes Schwarze (Jahrbücher für Nationalökonomie und Statistik, 2007)
The premium rates paid for statutory health insurance in Germany play a key role in the competition among health care funds. With the most recent health care reform (GKV-Wettbewerbsstärkungsgesetz GKV-WSG), a range of new products have been introduced that could erode the advantageous selling proposition of the premium rates. In addition to the pure monetary incentive to change health insurance provider, the new products include aspects that are becoming increasingly important to insured persons, such as the assessment of their own morbidity and the level and quality of health care provision. We find that current morbidity, experiences in morbidity, and expectations about morbidity will gain in importance when choosing health care provider. Using micro-data for the years 1999 to 2004 from the German Socio-Economic Panel study (SOEP), we investigate the willingness to change health provider in a multivariate setting. The SOEP data will be matched with register information about premium rates of all statutory health insurance funds in Germany. Applying a multinomial logit model, we show that there are two prototypes of insured people who change funds. The characteristics of those who changed funds can be used to evaluate the future developments in statutory health insurance in Germany, assuming that customer mobility will continue to increase.
Keywords: 330; Gesundheitswesen; Reform; Krankenversicherung; Deutschland